2018
DOI: 10.1111/gcb.14046
|View full text |Cite
|
Sign up to set email alerts
|

High land‐use intensity exacerbates shifts in grassland vegetation composition after severe experimental drought

Abstract: Climate change projections anticipate increased frequency and intensity of drought stress, but grassland responses to severe droughts and their potential to recover are poorly understood. In many grasslands, high land-use intensity has enhanced productivity and promoted resource-acquisitive species at the expense of resource-conservative ones. Such changes in plant functional composition could affect the resistance to drought and the recovery after drought of grassland ecosystems with consequences for feed pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
139
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(169 citation statements)
references
References 78 publications
28
139
2
Order By: Relevance
“…Instead, we found that drought resistance of forbs promoted total plant biomass resistance. This confirms the importance of plant functional groups for grassland responses to drought (Fry et al, ; Stampfli et al, ).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Instead, we found that drought resistance of forbs promoted total plant biomass resistance. This confirms the importance of plant functional groups for grassland responses to drought (Fry et al, ; Stampfli et al, ).…”
Section: Discussionsupporting
confidence: 79%
“…Our simulation of severe summer drought across eight permanent grasslands demonstrated differences in the drought responses of above‐ground plant biomass and soil microbial biomass. Rainfall exclusion for a duration which has not recurred in 50 years (except for sites in the Central Alps, Stampfli et al, ), caused strong decreases in plant biomass at the end of drought, in line with previous field drought experiments (Hoover et al, ; Kahmen et al, ; Stampfli et al, ). Severe drought also decreased forage quality (increased plant C:N ratio), consistent with drought‐induced changes in plant physiology and leaf senescence (Van der Molen et al, ).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations